Bovine Coronavirus Nonstructural Protein 1 (p28) Is an RNA Binding Protein That Binds Terminal Genomic cis-Replication Elements - Gustin, Kortney M. (American Society for Microbiology (ASM), 2009)
Nonstructural protein 1 (nsp1), a 28-kDa protein in the bovine coronavirus (BCoV) and closely related mouse hepatitis coronavirus, is the first protein cleaved from the open reading frame 1 (ORF 1) polyprotein product of genome translation. Recently, a 30-nucleotide (nt) cis-replication stem-loop VI (SLVI) has been mapped at nt 101 to 130 within a 288-nt 5′-terminal segment of the 738-nt nsp1 cistron in a BCoV defective interfering (DI) RNA. Since a similar nsp1 coding region appears in all characterized groups 1 and 2 coronavirus DI RNAs and must be translated in cis for BCoV DI RNA replication, we hypothesized that nsp1 might regulate ORF 1 expression by binding this intra-nsp1 cistronic element. Here, we (i) establish by mutation analysis that the 72-nt intracistronic SLV immediately upstream of SLVI is also a DI RNA cis-replication signal, (ii) show by gel shift and UV-cross-linking analyses that cellular proteins of ∼60 and 100 kDa, but not viral proteins, bind SLV and SLVI, (SLV-VI) and (iii) demonstrate by gel shift analysis that nsp1 purified from Escherichia coli does not bind SLV-VI but does bind three 5′ untranslated region (UTR)- and one 3′ UTR-located cis-replication SLs. Notably, nsp1 specifically binds SLIII and its flanking sequences in the 5′ UTR with ∼2.5 μM affinity. Additionally, under conditions enabling expression of nsp1 from DI RNA-encoded subgenomic mRNA, DI RNA levels were greatly reduced, but there was only a slight transient reduction in viral RNA levels. These results together indicate that nsp1 is an RNA-binding protein that may function to regulate viral genome translation or replication but not by binding SLV-VI within its own coding region.